2022
DOI: 10.3389/fpsyg.2022.881418
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes of Women and Men Across Gender Subgroups

Abstract: In this paper, we argue for the value of studying gender stereotypes at the subgroup level, combining insights from the stereotype content model, social role theory, and intersectional perspectives. Empirically, we investigate the stereotype content of gender subgroups in Norway, a cultural context for which a systematic description of stereotypes of gender subgroups is lacking. In a pilot study (n = 60), we established salient subgroups within the Norwegian context. Employing the stereotype content model, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The finding for the total role fit index is in line with Renström et al ( 2021 ), who found that women lecturers are not perceived differently from men lecturers by students. Furthermore, it supports the findings of Bye et al ( 2022 ) that women academics are not only perceived as similar to men academics but are also rated higher in some attributes. Even though the total role fit is higher for women academics, the range of the role fit indicates that women might be perceived more controversially than men.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The finding for the total role fit index is in line with Renström et al ( 2021 ), who found that women lecturers are not perceived differently from men lecturers by students. Furthermore, it supports the findings of Bye et al ( 2022 ) that women academics are not only perceived as similar to men academics but are also rated higher in some attributes. Even though the total role fit is higher for women academics, the range of the role fit indicates that women might be perceived more controversially than men.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, men perceive a higher role fit for men academics. Even though the regression models with women's role fit as a dependent variable do not show significant effects for gender, the effects in the other models support findings that men perceive a stronger role incongruity between women and the work in academia (Carli et al, 2016), while women perceive a higher role fit for women academics (Bye et al, 2022). The results support previous literature that men perceive stronger gender-science stereotypes (Symth and Nosek, 2015), resulting in the perception of a higher role fit for men academics.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This is consistent with previous research on traditional marketing channels such as advertising, where there is no significant difference in evaluations of spots in male product advertisements regardless of whether a male or female voice is used ( Whipple and McManamon, 2002 ). This may be due to the fact that for male products, female characteristics such as helpfulness, gentleness, and good listening skills provide a certain amount of warmth ( Bye et al, 2022 ), which will be then transferred to consumers’ perceptions of the product. This neutralizes the negative impact of gender conflict on consumers’ purchase intentions in the non-stereotypical gender role endorsement context to some extent.…”
Section: Discussionmentioning
confidence: 99%